Shock and paw - Conte, Cate (Conte, Cate. Cat Cafe mystery, 2024)
It’s the holiday season on Daybreak Island, and Maddie James is looking forward to stepping out of the limelight, watching the island’s Christmas decoration competition from afar, spending time with her boyfriend and family, running tours for visitors as part of the festivities and spreading holiday cheer through cute cats in jingle bell collars. But trouble hits close to home when word gets out that Donna Carey, the publisher of the island’s only daily newspaper where Maddie’s best friend Becky is editor, may be selling the business. Becky is a diehard journalist and to her, selling the only newspaper on the island is a fate worse than death. She publicly opposes the potential sale, wreaking havoc on her relationship with her big boss. Maddie is sympathetic, but she has her own problems - like getting pulled into a role on the Christmas event committee despite her best efforts to stay far removed, and solving the case of a mysterious cat breeder trying to sell expensive designer cats as holiday gifts on the island. But then Donna winds up dead―electrocuted by her own Christmas decorations―and it appears to be more than an accident. To make matters worse, Becky becomes suspect number one. Maddie is thrown into another murder investigation in order to save her best friend from a Christmas behind bars.